Application framework of tele-appointment system for teleprimary care / Mohd Raffiek Tahir - Tahir, Mohd Raffiek (2005)
The online appointment system allows anyone either targeted or not to manage their own appointment list, request and history. Tele-Appointment system is focussed on this to make patients can manage their own appointment. Although it is targeted to the patients registered in TelePrimary Care(TPC) application, which is one of the component from the Telemedicine of Multimedia Super Corridor(MSC), The system is an opportunity to explore the online system that can be integrated and used with the TPC application. A previous track, TPC is not exposed to internet connection since it is being used through internal wide area network(WAN). The exploration on the Tele- Appointment can expose TPC to more internet based system, hence the deliverable of TPC may expand not only for staffs in hospital and health centres but also the involvement of patients themselves. The proposed application framework consists of reviewing and constructing application design, application architecture and determining use case, actor and the flow of event of the system. This Tele- Appointment was an idea to enhance the appointment management because the appointment module that existed in TPC is restricted from public. Thus, Tele- Appointment is a gateway to open the usage and utilisation of TPC to public.